Reagent-Free Intramolecular Hydroamination of Ynone-Tethered Aryl-sulfonamide: Synthesis of Polysubstituted 4-Quinolones - Jung, Chanhyun; Hwang, Jinha; Lee, Kwanghee; Viji, Mayavan; Jang, Hongjun; Kim, Hyoungsu; Song, Sukgil; Rajasekar, Shanmugam; Jung, Jae Kyung (Journal of Organic Chemistry, 2024)
An efficient reagent-free method for the synthesis of polysubstituted 4-quinolone from 2-substituted alkynoyl aryl-sulfonamide was developed. This developed method tolerates various functional groups and gives the corresponding 4-quinolones. We have successfully extended this method to the synthesis of dihydro-4-quinolones from 2-alkenoyl aryl sulfonamide derivatives.
Keywords: Functionals; Intramolecular hydroamination; Quinolones; Reagent-free; Sulfonamide derivatives; Sulphonamides